Learning ArcGIS Geodatabases. - Nasser, Hussein (Packt Publishing, 2014)
This is a solution-based book, showcasing the real power of ArcGIS Geodatabase by following a real-world, example-based approach. This book is aimed at geospatial developers who want to work with ArcGIS Geodatabase as well as manage them. Having knowledge of building a Geodatabase from scratch isn't a must; Learning ArcGIS Geodatabases is ideal for those who want to use ArcGIS Geodatabase for the first time, or for those who want to migrate from their existing legacy database to a Geodatabase.